Abstract of Colenso on the Pentateuch: [a comprehensive summary of Bishop Colenso's argument, proving that the Pentateuch is not historically true; and that it was composed by several writers, the earliest of whom lived in the time of Samuel, from 1100 to 1060 B.C., and the latest in the time of Jeremiah, from 641 to 624 B.C.] - Colenso, John William, 1814-1883. (Tufts University. Tisch Library., 2022)
"The nation and country of the Jews. By W.H.B. [i.e. William Henry Burr]": pages [39]-48